2019
DOI: 10.3390/ani9050268
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study: Depriving Piglets of Maternal Feces for the First Seven Days Post-Partum Changes Piglet Physiology and Performance before and after Weaning

Abstract: Coprophagy has been described in piglets although its importance has not been fully assessed. The aim of this study was to evaluate how deprivation of maternal feces influenced piglet physiology, behavior, and performance. Eight litters were randomly assigned to one of two treatments. Control (CON) litters had access to maternal feces while deprived (DEP) litters were deprived of maternal feces for the first 7 d post-partum. Piglet behavior was quantified for 24 h at 7 d of age. Blood samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
18
2
Order By: Relevance
“…Although not fully studied, scientists believed that coprophagy helps piglets to prevent anaemia 3,[6][7][8][9][10][11] . In a previous study, we found that piglets deprived of maternal faeces for their first seven days of age had lower growth rate than those exposed to maternal faeces early in life 12 . In this study, we speculated that, as in rats, maternal semiochemicals might be attracting piglets and inducing coprophagy 12 .…”
Section: Identification Of Faecal Maternal Semiochemicals In Swine (Smentioning
confidence: 75%
See 2 more Smart Citations
“…Although not fully studied, scientists believed that coprophagy helps piglets to prevent anaemia 3,[6][7][8][9][10][11] . In a previous study, we found that piglets deprived of maternal faeces for their first seven days of age had lower growth rate than those exposed to maternal faeces early in life 12 . In this study, we speculated that, as in rats, maternal semiochemicals might be attracting piglets and inducing coprophagy 12 .…”
Section: Identification Of Faecal Maternal Semiochemicals In Swine (Smentioning
confidence: 75%
“…In a previous study, we found that piglets deprived of maternal faeces for their first seven days of age had lower growth rate than those exposed to maternal faeces early in life 12 . In this study, we speculated that, as in rats, maternal semiochemicals might be attracting piglets and inducing coprophagy 12 . However, to date, changes in the nutritional value of lactating sow faeces and in its volatile profile has not been evaluated.…”
Section: Identification Of Faecal Maternal Semiochemicals In Swine (Smentioning
confidence: 75%
See 1 more Smart Citation
“…This is to be expected as the diet changes significantly post-weaning. Alternately, piglets are known to exhibit coprophagy [34], which in turn would aid in the development of the microbiota and suggests that this change may be a function of natural gut maturation as piglets age.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the importance of farrowing crate cleanliness but also highlight the possible impact of sow faeces on the initial bacteria colonising the GIT. Indeed, piglets are born onto the region of the crate where the sow urinates and defecates, however, whether this is positive or negative is yet to be elucidated as studies within our research group and others are conflicting [ 44 ]. Previous studies have also documented the high prevalence of potentially pathogenic bacteria in early life, particularly in regard to C. perfringens in pigs [ 39 , 45 ].…”
Section: Discussionmentioning
confidence: 99%